2018
DOI: 10.1177/1532440018759269
|View full text |Cite
|
Sign up to set email alerts
|

Extra, Extra, (Don't) Roll-off about It! Newspaper Endorsements for Ballot Measures

Abstract: Voters often have difficulty making choices on the myriad state constitutional amendments they vote on each year. Without partisan cues, they turn to other sources for these low-salience, high complexity measures. One such source is newspaper endorsements. In this article, we look at newspaper endorsements of ballot measures in Florida over 20 years both on “no” votes and roll-off. We argue that endorsements' effect on “no” votes and roll-off differs in ways not previously appreciated. Newspaper endorsements h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Previous literature examining the impact of endorsements on specific elections indicates the importance of considering the type of endorser. Studies have considered the effectiveness of endorsements from groups or organizations such as newspapers (Fahey et al, 2018), political parties (Kousser et al, 2015), and advocacy groups (Gerber and Phillips, 2003). Others have examined the effectiveness of endorsement provided by an individual such as a celebrity or a political figure (Jackson and Darrow, 2005;Vining and Wilhelm, 2011).…”
Section: Impact Of Endorsementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature examining the impact of endorsements on specific elections indicates the importance of considering the type of endorser. Studies have considered the effectiveness of endorsements from groups or organizations such as newspapers (Fahey et al, 2018), political parties (Kousser et al, 2015), and advocacy groups (Gerber and Phillips, 2003). Others have examined the effectiveness of endorsement provided by an individual such as a celebrity or a political figure (Jackson and Darrow, 2005;Vining and Wilhelm, 2011).…”
Section: Impact Of Endorsementsmentioning
confidence: 99%
“…Similarly, the use of political endorsements is a long-established campaign tactic that has endured, in part, because of the way campaigns have adapted such endorsements to extend their salience, relevancy, and effectiveness. Often, the success of a political endorsement is attributed to the persuasiveness and effectiveness of the endorser, whether it be an organization (i.e., political party, newspaper, media outlet), a celebrity, or a political elite (Jackson and Darrow, 2005;Chou, 2015;Fahey et al, 2018). However, beyond the source, general persuasion research argues that the message itself contributes to the effectiveness of any persuasive message such as endorsement statements (Perloff, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, these bonds may be used to raise money for schools, libraries, senior citizen facilities, transportation projects, community pools, fire houses, mental health facilities, or affordable housing. Ballot measures of all kinds are notoriously difficult to decipher; they are often worded in legalese and contain perplexing double negatives, making it difficult for voters know what a "yes" or "no" vote actually means (Fahey et al, 2018). Researching what will be on the ballot ahead of time can be helpful in this regard.…”
Section: Ballot Measuresmentioning
confidence: 99%
“…Since the candidate names typically come first, voters may tire by the time they reach the ballot measures. One study in California found a declining number of "yes" votes for each additional ballot measure listed; this rolloff was attributed to voters either giving up before completing the entire ballot or voting "no" due to voter fatigue (Fahey et al, 2018).…”
Section: Ballot Measuresmentioning
confidence: 99%